Unraveling the interconnectedness between physician burnout and symptoms of depression, anxiety, and stress: a network analysis among Chinese psychiatrists - Wang, Song; Gu, Mengyue; Zhang, Shujing; Gu, Jingyang; Shi, Yudong; Yang, Yating; Zhang, Ling; Li, Mengdie; Xia, Lei; Jiang, Feng; Liu, Huanzhong; Tang, Yi-lang (Frontiers in Public Health, 2025)
BackgroundThe COVID-19 pandemic significantly increased the levels of burnout and symptoms of depression, anxiety, and stress among healthcare professionals. However, research on the interrelations between burnout and psychological symptoms is scarce, particularly among psychiatrists. This study addresses this gap in a national sample.MethodData was collected via an online survey conducted in Mainland China from January to March 2021 with a sample size of 3,783 participants. Psychological symptoms were assessed using the Depression, Anxiety, and Stress Scale-21 (DASS-21), and physician burnout was assessed using the Maslach Burnout Inventory-Human Service Survey (MBIHSS). Network analysis was used to examine the interconnection between physician burnout and psychological symptoms, with further analysis conducted on multiple levels, including individual symptoms in central positions or acting as bridges between clusters, and identifying core symptom combinations with significant correlations.ResultsStress emerged as the highest Expected Influence (EI) index, with emotional exhaustion in the burnout cluster being the singular bridge symptom. Furthermore, depressive symptoms such as hopelessness and anhedonia showed a strong and the most straightforward association with emotional exhaustion, while stress-related overreaction was closely associated with depersonalization.ConclusionNetwork analysis between burnout and psychological symptoms identified critical symptoms like stress and emotional exhaustion in Chinese psychiatrists. Close monitoring of these symptoms may be crucial for mitigating the risk of common psychological disturbances and preventing their exacerbation in this population.